Unit root tests for time series with level shifts: A comparison of different proposals - Markku Lanne; Helmut Lütkepohl (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
A number of unit root tests which accommodate a deterministic level shift at a known point in time are compared in a Monte Carlo study. The tests differ in the way they treat the deterministic term of the DGP. It turns out that Phillips-Perron type tests have very poor small sample properties and cannot be recommended for applied work. Moreover, tests which estimate the deterministic term by a GLS procedure under the unit root null hypothesis are superior in terms of size and power properties relative to tests which estimate the deterministic term by OLS procedures.
urn:nbn:de:kobv:11-10048579
Keywords: C22; C12; 330; Univariate time series; unit root; structural shift; autoregression